ANTI-VANDALISM SYSTEM FOR MONITORING SMART LEVEL CROSSING PROPERTY: A COMPREHENSIVE REVIEW - M. Rosyidi; Thiya Fiantika; Novi Irawati; Sinung Nugroho (Majalah Ilmiah Pengkajian Industri, 2020)
This research addresses the problem of vandalism incident related to the smart level crossing technology. Smart level crossing system is essential as a safety system inside the level area, because of that any failure related to the System will endanger the railway and road user. Another subsystem that protects smart level crossing property is critical. This research will show the plan for applying anti-vandalism technology and analysis another possibility of technology related to the System. Keywords: Vandalism, Smart, Level crossing, Subsystem, Railway.